2005
DOI: 10.1103/physrevb.71.094517
|View full text |Cite
|
Sign up to set email alerts
|

Andreev magnetotransport in low-dimensional proximity structures: Spin-dependent conductance enhancement

Abstract: We study the excess conductance due to the superconducting proximity effect in a ballistic two-dimensional electron system subject to an in-plane magnetic field. We show that under certain conditions the interplay of the Zeeman spin splitting and the effect of a screening supercurrent gives rise to a spin-selective Andreev enhancement of the conductance and anomalies in its voltage, temperature and magnetic field characteristics. The magnetic-field influence on Andreev reflection is discussed in the context of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Tunneling into these supercurrents shifts the momentum of the quasiparticles and ultimately their energy. Since this only occurs forsuperconducting quasiparticles, the observation of the Doppler effect confirms the presence of Andreev reflection, as established in numerous theoretical and experimental works [44,45,[47][48][49][50][51][52][53][54][55][56][57].…”
Section: Methodssupporting
confidence: 77%
“…Tunneling into these supercurrents shifts the momentum of the quasiparticles and ultimately their energy. Since this only occurs forsuperconducting quasiparticles, the observation of the Doppler effect confirms the presence of Andreev reflection, as established in numerous theoretical and experimental works [44,45,[47][48][49][50][51][52][53][54][55][56][57].…”
Section: Methodssupporting
confidence: 77%
“…Interestingly, differential conductance measurements in some of our Bi 2 Sr 2 CaCu 2 O 8+δ (Bi-2212)/Bi 2 Te 2 Se devices exhibit a zero-bias conductance peak (ZBCP) that behaves quite differently from previous experimental observations and theoretical predictions (Fig.1A). Previous theoretical and experimental studies of various ZBCPs: Andreev bound states (ABS), coherent Andreev reflection (CAR), weak antilocalization (WAL), Andreev reflection, proximity effect, Kondo effect, magnetic impurities, and Majorana fermions have established that the ZBCP should split in applied magnetic field, appear at T c , be broadened with temperature, and/or its height depends strongly on the orientation of the applied field 9,10,15,[23][24][25] . The ZBCP we observe in mechanicallybonded Bi 2 Sr 2 CaCu 2 O 8+δ (Bi-2212)/Bi 2 Te 2 Se devices are suppressed at the same rate in different magnetic field orientations (Fig.…”
Section: I Introductionmentioning
confidence: 99%
“…The Andreev reflection probability at zero field was less than unity, typically around p AR (B = 0) = 0.6, in agreement with the finite value of Z. More recently, the magnetic field dependence of Andreev reflection was treated in a theoretical paper [32]. It was shown that the induced gap in the semiconductor depends on screening currents in the superconductor and that Andreev reflection indeed depends on the magnetic field.…”
Section: Andreev Reflection and Chaotic Motionmentioning
confidence: 62%